2016
DOI: 10.24297/jbt.v6i1.4016
|View full text |Cite
|
Sign up to set email alerts
|

Bio-ethanol production from sweet potato using co-culture of saccharolytic molds (Aspergillus spp.) and Saccharomyces cerevisiae MTCC170

Abstract: In the present study, sweet potato which are in abundance and do not interfere with food security was subjected to simultaneous saccharification and fermentation process by co-culture of Aspergillus spices and Saccharomyces cerevisiae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The composition of selected agro-industrial residues and wastes, employed for the cultivation of microorganisms that can produce lipases, is presented in Table 3. Despite this fact, agro-industrial residues and waste, such as bran, straw, molasses, peels, seeds, pomace, waste water and oil cakes, can be used for the production of various value-added products, for example, for the production of industrially important enzymes such as lipases [72], biofuels [73], antibiotics [74], mushrooms [75] and also various useful chemicals [76].…”
Section: Agro-industrial Residues and Wastes For Lipase Productionmentioning
confidence: 99%
“…The composition of selected agro-industrial residues and wastes, employed for the cultivation of microorganisms that can produce lipases, is presented in Table 3. Despite this fact, agro-industrial residues and waste, such as bran, straw, molasses, peels, seeds, pomace, waste water and oil cakes, can be used for the production of various value-added products, for example, for the production of industrially important enzymes such as lipases [72], biofuels [73], antibiotics [74], mushrooms [75] and also various useful chemicals [76].…”
Section: Agro-industrial Residues and Wastes For Lipase Productionmentioning
confidence: 99%
“…Previous studies revealed the production of biofuels from positive agro-industrial residues like rice straw, sweet potato waste, sawdust, potato waste, corn stalks, sugarcane bagasse, and sugar beet waste Kumar et al 2014Kumar et al , 2016. In 2011, all over the world bioethanol production increased as showed by the production of 85 billion liters of bioethanol (Avci et al 2013;Saini et al 2014).…”
Section: Bio Fuel Productionmentioning
confidence: 99%
“…Fruit wastes constitute high reducing sugars, used for the production of bio-ethanol [ 217 ]. Whereas, the composition of vegetable wastes are high in cellulose, hemicelluloses, and lignin, which are used for the production of second-generation bioethanol [ 218 , 219 , 220 ].…”
Section: Uses Of Fermentation For the Production Of Bioactive/valumentioning
confidence: 99%